Impact of entrepreneurship intention on socio-economic uplift: Moderating role of entrepreneurial infrastructure for home-based start-ups - Shahjahan Sarfraz Raja; Valliappan Raju; Shahnawaz Sarfraz Raja (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2021)
The main objective of this research work is to investigate moderating effect of entrepreneurial infrastructure on entrepreneurial intention and socio-economic uplift. The hypotheses have been developed after reviewing the literature thoroughly. The data is collected from 205 household respondents of village Khanwal, tehsil and district Chakwal, Pakistan. For data collection, self-administered questionnaires were distributed to initiators from every household for research study. The reason for involving every household is to ensure inclusive growth of village community. By using SmartPLS software, partial least squares based structural equation modeling was used and it was found that entrepreneurial intention (EI) has positive influence on socio-economic uplift (SEUP) and entrepreneurial infrastructure plays a moderating role in relationship of entrepreneurial intention with socio-economic uplift. This study is helpful for shaping public policy to achieve more shared prosperity through providing entrepreneurial infrastructure specifically capital through microfinance system for creating income earning opportunity. This is the first study of its kind which tries to bridge the existing research gap related to the moderating role of entrepreneurial infrastructure in strengthening the relationship of entrepreneurship intention with socio-economic uplift in the emerging economy of Pakistan.
Keywords: 330; entrepreneurial infrastructure; socio-economic uplift; entrepreneurialintention; Pakistan